The Effect of Organizational Activity and Self-efficacy on Work Readiness - Asiya Asiya; Nadya Novia Rahman (Dinasti Publisher, 2025)
This study aims to determine the effect of Organizational Activityand self-efficacy on work readiness. This research method uses a quantitative approach. The subjects in the study were 95 students of the Faculty of Economics and Business, Mulawarman University and students of SMK Negeri 1 Penajam Paser Utara. The data collection method uses three types of scales, namely the work readiness scale, Organizational Activity scale and self-efficacy scale. The results showed that: (1) there is a significant influence of Organizational Activity and self-efficacy on work readiness with the value of F count = 922.620> F table = 3.09 and p value = 0.000 and has an influence contribution (R2) of 95%. (2) there is a significant positive effect of Organizational Activity on work readiness with a beta coefficient (?) = 0.330, t count = 5.089 > t table = 1.986, and p value = 0.000 (p < 0.05). (3) there is a significant positive effect of self-efficacy on work readiness with a beta coefficient value (?) = 0.660, t count = 10.174 > t table = 1.986, and p value = 0.000 (p < 0.05).